2022
DOI: 10.1007/s11418-022-01647-w
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease

Abstract: Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata, showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…As a major organ for aliphatic acid synthesis and metabolism, the liver has the ability to synthesize, break down, and metabolize aliphatic acids ( Heeren and Scheja, 2021 ). In certain pathological states, such as obesity, hyperlipidemia, and hepatic fibrosis, the liver is susceptible to excessive lipid accretion ( Ran et al, 2023 ). Adipocyte proliferation, white blood cell infiltration, and cytokine release can induce the deposition and accretion of lipids in hepatocytes, exacerbating the occurrence and progression of hepatic fibrosis ( Suganami et al, 2012 ; van der Windt et al, 2018 ; Heeren and Scheja, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a major organ for aliphatic acid synthesis and metabolism, the liver has the ability to synthesize, break down, and metabolize aliphatic acids ( Heeren and Scheja, 2021 ). In certain pathological states, such as obesity, hyperlipidemia, and hepatic fibrosis, the liver is susceptible to excessive lipid accretion ( Ran et al, 2023 ). Adipocyte proliferation, white blood cell infiltration, and cytokine release can induce the deposition and accretion of lipids in hepatocytes, exacerbating the occurrence and progression of hepatic fibrosis ( Suganami et al, 2012 ; van der Windt et al, 2018 ; Heeren and Scheja, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic expression of the FATP can significantly increase during the pathogenesis of NAFLD. Overexpression of FATP1, FATP2, and FATP3 has been confirmed at the hepatic mRNA level in a high-fat diet (HFD)-fed mouse model [40]. CD36 is another well-known FFA transporter overexpressed in NAFLD.…”
Section: Overexpression Of Fa Transportersmentioning
confidence: 96%
“…As well as carrying out its function as a fatty acid transporter, FATP5 can also activates long-chain fatty acids (LCFAs) through covalent coenzyme A attachment [ 56 ]. It has been reported that deletion or silencing of FATP5 reduces triglyceride levels in the liver and ameliorates diet-induced steatosis in rats [ 57 ]. The FATP5 variant rs56225452 gain-of-function was found to be associated with an increased risk of hepatic steatosis, elevated ALT levels, and enlarged insulin resistance [ 58 ].…”
Section: Metabolic-related Genes Influencing Nafldmentioning
confidence: 99%